Differences in sleep disturbances among offspring of parents with and without bipolar disorder: association with conversion to bipolar disorder. (7th November 2015) - Levenson, Jessica C; Axelson, David A; Merranko, John; Angulo, Melina; Goldstein, Tina R; Goldstein, Benjamin I; Brent, David A; Diler, Rasim; Hickey, Mary Beth; Monk, Kelly; Sakolsky, Dara; Kupfer, David J; et al.
Abstract : Objectives: Disruptions in sleep and dysregulation in circadian functioning may represent core abnormalities in the pathophysiology of bipolar disorder (BP). However, it is not clear whether these dysfunctions are state or trait markers of BP. This report compared sleep and circadian phenotypes among three groups: offspring of parents with BP diagnosed with BP at intake (BP/OB; n = 47), offspring of parents with BP without BP at intake (non‐BP/OB; n = 386), and offspring of matched control parents who did not have BP (controls; n = 301). We also examined the association of baseline sleep parameters with subsequent development of BP among the non‐BP/OB group. Methods: Pittsburgh Bipolar Offspring Study youth (ages 6–18 years) and their parents completed assessments every two years pertaining to the child's sleep and circadian phenotypes and current psychopathology. Mixed‐effects models examined differences in baseline sleep and circadian variables among the three groups. Results: BP/OB offspring who were in a mood episode differed significantly on sleep parameters from the non‐BP/OB and the offspring of controls, such as having inadequate sleep. Mixed logistic regression procedures showed that baseline sleep and circadian variables, such as frequent waking during the night, significantly predicted the development of BP among non‐BP/OB over longitudinal follow‐up. Conclusions: While lifetime diagnostic status accounted for differences among the groups in sleep and circadian disturbances, psychopathology explained the differences even further. Additionally, sleep disturbance may be a prognostic indicator of the development of BP in high‐risk youth. Future studies are required to further disentangle whether sleep and circadian disruption are state or trait features of BP.